Nonionizing Electromagnetic Field: A Promising Alternative for Growing Control Yeast - Ganga-Munoz, M; Chavez-Rosales, R; Rodriguez-Garcia, A; Peña-Bernales, R; Gil-Duran, C (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In the food industry, some fungi are considered to be common spoilage microorganisms which reduce the shelf life of products. To avoid this outcome, different technologies are being developed to control their growth. Electromagnetic fields (EMF) have been used to combat bacterial growth, but there are few studies on yeasts and their possible action mechanisms. For this reason, we studied the effect of EMF between 1 to 5.9 GHz bands on the growth of Saccharomyces cerevisiae yeast and observed that all the frequencies of the band used cause the reduction of the viability of this yeast. In addition, we observed that the distance between the antenna and the sample is an important factor to consider to control the growing yeast. By using transmission electron microscopy, we found that the EMF caused a loss of continuity of the yeast cell membrane. Therefore, EMF may be used as a control method for yeast growth. © 2021 by the authors.
Keywords: electromagnetic fields; food quality; membrane disruption; radiofrequency waves; Saccharomyces cerevisiae; spoilage control